The homestead - Byler, Linda (New York, New York : Good Books, 2017)
Fifteen-year-old Hannah and her family move from Lancaster, Pennsylvania to North Dakota, where they face harsh realities far from any Amish communities, forcing her to work on a cattle ranch, where she meets a charismatic English boy named Clay Jenkins.
Keywords: Knopp, Joyce -- Memorial; Amish -- Fiction; Christian life -- Fiction; Amish; Christian life; North Dakota -- History -- Fiction; North Dakota; Christian fiction; Religious fiction; Fiction; History